2021
DOI: 10.7577/njcie.4257
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of cyberethics: A comparative study of preservice teachers in Malta, Norway, and Spain

Abstract: This paper explores the knowledge and understanding of cyberethics held by preservice teachers across three European countries. The study was conducted via an online survey and yielded a total of 1,131 responses from preservice teachers in Spain, Norway, and Malta. The facets of cyberethics included in this study were specifically related to behaving responsibly online, safeguarding privacy, respecting copyright, seeking consent of third parties before posting images or videos on social media platforms, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
(32 reference statements)
2
9
0
Order By: Relevance
“…Similarly, a survey study, focused on copyright and privacy in social media carried out with PSTs in Malta, Norway, and Spain ( N = 1,131), found that, overall, participants from the three countries showed a lack of awareness of responsible behavior and of knowledge in terms of copyright and privacy in social media, but with significant differences in awareness between countries (Milton et al, 2021 ). The authors of this study recommend that all teacher education programs should include copyright and privacy in social media contexts in their curricula.…”
Section: Literature Reviewmentioning
confidence: 98%
See 4 more Smart Citations
“…Similarly, a survey study, focused on copyright and privacy in social media carried out with PSTs in Malta, Norway, and Spain ( N = 1,131), found that, overall, participants from the three countries showed a lack of awareness of responsible behavior and of knowledge in terms of copyright and privacy in social media, but with significant differences in awareness between countries (Milton et al, 2021 ). The authors of this study recommend that all teacher education programs should include copyright and privacy in social media contexts in their curricula.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Teachers’ and PSTs’ social media use, and associated data privacy issues, can be related to contextual norms and backgrounds (e.g., university and schooling context, local context, teacher’s values; see Prestridge et al, 2021 ; Greenhalgh et al, 2021 ; Milton et al, 2021 ), and national cultural values and variables (Hofstede, 2001 , 2010 ; Ronen & Shenkar, 2013 ). To shed light on differences related to the countries of the PSTs in our sample, in what follows we make cautious use of Hofstede’s ( 2001 , 2010 ) cultural dimensions to explain some cultural differences in educational contexts, acknowledging the existence of diverse cultural backgrounds beyond Hoftstede’s dimensions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations